MENINGKATKAN KEMAMPUAN MENGENAL KOSA KATA PADA ANAK MELALUI MODEL ATIK PADA ANAK USIA DINI - Intan Yusmarini; Sri Watini (LPPM Universitas Bina Bangsa, 2022)
Vocabulary is an important element in the development of language skills in early childhood. The development of vocabulary comprehension skills requires a complete understanding of the child. This study hopes to improve children's ability to recognize vocabulary in children using the ATIK learning model in group A at Abdi Pertiwi Kindergarten. This research method uses quantitative methods. The sample of this study involved 20 children in group A. The data collection process in this study was carried out in two stages. The results of this research action have shown an increase in the child's ability to recognize vocabulary and show an increase that has been made in the first stage which shows a result of 61.1% where half of the sample has shown an increase, then in the second action the actions that have been taken show an increase again by 91.1%. The researcher concludes that the researcher's efforts to improve vocabulary skills in children through the ATIK model are well applied in Abdi Pertiwi Kindergarten